The importance of early bonding on the long-term mental health and resilience of children. Issue 1 (2nd January 2016) - Winston, Robert; Chicot, Rebecca
Abstract: Human babies are born very dependent on their parents. They undergo huge brain development, growth and neuron pruning in the first two years of life. The brain development of infants (as well as their social, emotional and cognitive development) depends on a loving bond or attachment relationship with a primary caregiver, usually a parent. There is increasing evidence from the fields of development psychology, neurobiology and animal epigenetic studies that neglect, parental inconsistency and a lack of love can lead to long-term mental health problems as well as to reduced overall potential and happiness. In this paper, the authors consider the evidence for this claim across several disciplines and conclude that the support of babies and their parents in the first two years of life to be a crucial aim of public health groups in the community.